Leadership today : practices for personal and professional performance - Marques, Joan; Dhiman, Satinder (Springer texts in business and economics, 2017)
This textbook provides a clear understanding of leadership needs in today's business world, explained within the scope of hard and soft leadership skills. It captures qualities and skills such as spirituality, empathy, moral behavior, mindfulness, empathy, problem solving, self-confidence, ambition, knowledge, global understanding, and information technology. This text explains and provides guidelines for the implementation of each skill and includes examples from contemporary and historical leaders inviting the reader to consider each quality and engage in self-reflection. This book deviates from excessive theoretical descriptions presenting a timely, hands-on approach to leadership. Even though leadership, as a phenomenon, has been studied extensively in the past decades, it remains a challenge as times, needs, and perceptions change and the world increasingly merges into a global village. Numerous leadership styles have been developed, varying from resonant, servant, and laissez faire, to authentic, authoritative, and coercive; from charismatic and team, to transformational and transactional leadership. And while each leadership style harbors a wealth of qualities, strategies, and behavioral guidelines toward successful implementation, there are critical overarching themes that keep emerging, regardless of the "label" one chooses. In recent years, an important distinction has been established in leadership qualities: soft and hard skills. Soft skills are reflective in nature, and entail qualities such as empathy, motivation, self-awareness, self-regulation, and social skills. In leadership performance, the application of soft skills entails a combination of interpersonal and social skills. Hard skills are more of a measurable nature. They encompass analytical and technical skills. Both soft and hard skills are important for leaders because they complement one another. Featuring contributions form academics and professionals from around the world, this text will be of interest to students, researchers, professionals in business and leadership who aspire to lead beyond their immediate environment.